Karuna (compassion): The practice and its impacts on Chinese Mahayana Buddhists in Kuala Lumpur and Selangor - Mohd Nor, Nur Suriya (Jabatan Usuluddin Dan Falsafah, Fakulti Pengajian Islam Universiti Kebangsaan Malaysia, 2016)
KARUNA (compassion) in Mahayana Buddhism is explained as a wish to eliminate suffering from beings. It designates the quality of heart which emphasizes love and respect for all sentient beings. In Mahayana Buddhism compassion is equal to wisdom. In fact, it is one of the important ways to attain Nirvana (liberation from suffering). This paper seeks to discuss the practice of compassion and its impacts on Chinese Mahayana Buddhist Community in Kuala Lumpur and Selangor. The discussion is divided into two parts; the practice of filial piety and the practice of compassion towards other beings. It is found that the teaching of compassion in Mahayana Buddhism shares a lot of similarities with the teaching of compassion in Islam. It means that compassion stands as a common value between the two religions thus providing avenues for promoting mutual understanding between Buddhists and Muslims in Malaysia.